Urgensi Sumber Daya Alam dalam Ekonomi Islam - Dayu, Wulan; Nasution, M. Yasir; Sugianto, Sugianto (Jurnal Ilmiah Ekonomi Islam, 2024)
In the Koran, nature is described as a book compiled by a wise being, whose every line and word is a sign of the wisdom of its author. Of course, nature can no longer be separated from social life. Economic activities and social life are two interrelated things. In this case, economic activity is a human activity in order to fulfill all his life needs. In general, there are three types of economic activities, namely: production, distribution and consumption. These three things are mutually sustainable. In this modern era, economic activities are greatly influenced by government intervention and policies. Apart from that, this economic activity is influenced by natural resources, human resources, management systems and so on.